2015
DOI: 10.1007/s12078-015-9192-9
|View full text |Cite
|
Sign up to set email alerts
|

Iran Smell Identification Test (Iran-SIT): a Modified Version of the University of Pennsylvania Smell Identification Test (UPSIT) for Iranian Population

Abstract: The University of Pennsylvania Smell Identification Test (SIT) is the most cited olfactory test in the literature because it is easy to perform and there is high test-retest reliability. There were no standardized olfaction values in a normal Brazilian population. Aim: To measure the SIT score in a group of Brazilians, and to assess the level of difficulty when implementing the test. Study design: A cross-sectional study. Materials and Methods: The SIT was applied in 25 Brazilian volunteers of various income l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 25 publications
0
38
0
1
Order By: Relevance
“…Due to the culture-specific nature of smell perception, the reliability of these tests has to be evaluated in different populations (2) (37). Localized versions of the UPSIT test kit have been introduced in countries such as Brazil (23), Turkey (24), Lithuania (25), and Iran (16) (for an exhaustive review refer to (14)).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the culture-specific nature of smell perception, the reliability of these tests has to be evaluated in different populations (2) (37). Localized versions of the UPSIT test kit have been introduced in countries such as Brazil (23), Turkey (24), Lithuania (25), and Iran (16) (for an exhaustive review refer to (14)).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the mentioned assessment methods, previous studies have shown that olfactory deficit is an early symptom of Alzheimer’s disease (12) (13). Further studies have demonstrated that standard methods of assessing olfactory system such as sniffing kits can be helpful in distinguishing AD patients from healthy individuals (14) (15) (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with significantly lower levels of performance are determined as malingerers 6 . Iran Smell Identification Test (Iran-SIT) [17] , a standardized 40-item smell identification test is a modified version of UPSIT to assess the olfactory function of Iranian population considering cultural adaption. It has the adequacy to classify olfactory disorders into four levels: normosmia (the normal olfactory function), mild microsmia (mildly decreased olfactory function), severe microsmia (severely decreased olfactory function) and anosmia (loss of olfactory function).…”
Section: Iran Smell Identification Test (Iran-sit)mentioning
confidence: 99%
“…Other disadvantages that have decreased the clinical popularity of brain SPECT are high costs, unreliable supply of radiopharmaceuticals like Tc-99m, longer acquisition time which in turn increases the risk of patient motion and also dependency to patient preparation, cooperation and consciousness [15,17,19,20] .…”
Section: Brain Single Photon Emission Tomography (Spect)mentioning
confidence: 99%